Teaching Reading with KWL Strategy during Online Learning - Widyari, Ni Kadek Riska; Ratminingsih, Ni Made; Saputra, I Nyoman Pasek Hadi (Journal of Educational Study, 2022)
This current study aimed at investigating the effect of KWL strategy towards the reading comprehension of second grade students at SMA N 1 Kintamani in online learning. This research was an experimental research with pre-test and post-test control group design. By involving XI IPS 1 as the control group which taught by using conventional method and XI IPS 2 as the experimental group which taught by using KWL strategy in teaching reading. The obtained data were descriptively and inferentially analyzed by using SPSS 23.0. In pre-test, the study found the experimental group (M= 56.28) showed higher mean score of reading comprehension rather than the control group (55.87). The result of t-test also revealed that the mean difference between experimental and control group in pre-test was not significant (α=>0.05). Furthermore, in post-test the experimental group got better reading comprehension achievement than the control group. The result of the study found that the experimental group (M=74.32) got higher mean score of reading comprehension compared to control group (M= 61.16). The result of t-test also confirmed that the mean difference between experimental and control group in post-test was significant (α=<0.05. In conclusion, KWL strategy gave a significant effect on the reading comprehension of second grade students at SMAN 1 Kintamani.